Design of High-Speed Ipm-Bldc Motor with High Efficiency - Lee, Ho-Joon; Kang, Dong-Woo (International Journal of Engineering and Technology, 2018)
In recent years, there are many applications that use BLDC(Brushless DC) motors. Ranging from tens to hundreds of watts to several megawatts, from low-speed drive systems to high-speed drive systems. This paper describes the design of a BLDC motor for application to a system driven at about 800W class, 60,000rpm or more. Particularly discuss IPM(Interior Permanent Magnet) type BLDC rather than SPM(Surfaced Permanent Magnet) structure. An efficiency improvement design method for reducing iron loss and permanent magnet loss due to high-speed rotation will be described.Â Â